PENGUMPULAN ZAKAT MELALUI PAYROLL SYSTEM DITINJAU DARI PERSPEKTIF HUKUM ISLAM - Rosyidi, Imron (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2018)
This research  is conducted in order  to answer  the question how the review of Islamic law to the collection of zakat through  payroll system?  The  purpose of this study  is to investigate  how  the  review of Islamic law to the  collection  of zakat through  payroll system.  This research  is library research  that is by way of tracing,  collecting, clarifying and  viewing data  from various  literatures  related  to the core problems  in order  to get the principles and  concepts  about  the problems  as the object of research. The approach used in this research  is qualitative  normative clinical normative Islamic research  with fath adz-dzari’ah method. The results of this study  show  that  the collection  of zakat through  payroll system  is valid. Referring to the order  of zakat collection  to the ruler in Surat  At-Taubah verse 103  that to maximize  the collection  of zakat is something  that must be done  by the ruler, therefore  everything  that becomes the means  to maximize the collection must also be held, one  of them  is the method of collecting zakat through  payroll system.  Therefore  the collection  of zakat through  payroll system according  to fath adz-dzari’ah  is valid. Collection of zakat through  payroll system must intend  once every year at the beginning  of payment because it is a cicil system.